Optimization of wall components for encapsulation of Nigella sativa seed oil by freeze-drying - Makouie, Sina; Alizadeh, Mohammad; Maleki, Omid; Khosrowshahi, Asghar (Department of Technology of Agricultural product (THP) Jambi University, 2019)
The aim of the present study was to determine the proper concentrations of whey protein isolate (WPI), Arabic gum (AG), and Zedo gum (ZG) for the encapsulation of Nigella sativa seed oil (NSO). WPI, AG, and ZG were used as wall materials for the encapsulation of NSO by mixture design and then the optimum sample with minimum Z-average, PDI, and a* and maximum zeta potential, conductivity, encapsulation efficiency, and b* was selected for examining FT-IR and SEM. The findings demonstrated that lower particle size and particle dispersion index were obtained at higher amounts of AG and WPI with the least a*. Desirability function results indicate that the mixture of 39.05% WPI, 16.758% AG, and 4.192% ZG led to the production of the optimum sample. Microencapsulation of Nigella sativa seed oil using the optimum wall composition was recognized to be useful to preserve bioactive compounds and provide flavor stability, enabling the use of microcapsules in food formulations.